The Effect of Work-Life Balance and Workload on the Performance of Inpatient Installation Nurses at Pagelaran Cianjur Hospital - Amelia Putri; Mochamad. Vrans Romi (LP2M IAIN Palopo, 2026)
Nurse performance is one of the main indicators in determining the quality of hospital services. The high demands of health services require nurses to be able to provide professional, fast, and quality services. However, the high workload and difficulties in maintaining a work-life balance have the potential to affect nurses' performance. This condition was also found at Pagelaran Cianjur Hospital which was characterized by the presence of nurses who had sufficient performance categories, high levels of delays, and fluctuations in the number of patient visits which had an impact on increasing workload. This study aims to analyze the influence of work-life balance and workload on the performance of nurses at Pagelaran Cianjur Hospital, both partially and simultaneously. The research uses a quantitative approach with a survey method. The research population is all inpatient installation nurses of Pagelaran Cianjur Hospital totaling 34 people, which is also used as a research sample through saturated sampling techniques. Data were obtained through observation, interviews, documentation, and questionnaire deployment, then analyzed using multiple linear regression analysis with the help of IBM SPSS Statistics. Hypothesis testing was carried out using a partial test (t-test) and a simultaneous test (F-test). The results of the study showed that work-life balance did not have a significant effect on the performance of nurses. Workload has a significant effect on nurse performance according to the direction of the relationship shown by the results of regression analysis. In addition, work-life balance and workload simultaneously have a significant effect on the performance of nurses at Pagelaran Cianjur Hospital. The findings of the study show that improving work-life balance and proportional workload management are important factors in improving nurse performance so that it can support the improvement of hospital service quality.